SPIRITUALITAS IMAMAT DALAM BAYANG-BAYANG TANTANGAN PASTORAL (IMAM SEBAGAI PELAYAN DALAM TANTANGAN PASTORAL DI KEUSKUPAN TIMIKA) - Emanuel Richardus Buang Lela; Edison R.L. Tinambunan (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2020)
This article focuses on reflections of the priestly vocation as a minister in the context and pastoral situation in the Diocese of Timika. The approach is studying on ecclesiastical documents in regarding on the priesthood spirituality in serving of God's people. The purpose of this paper is to discover the high spirit of ministry of a priest who is based on the example of Jesus Christ as Teacher and Chief Pastor in the pastoral ministry of the Timika Diocese. Total service in dedicative involvement, a soothing presence, entering into the struggles of family life, and having the courage of dialoguing with anyone are a concrete service to realize the spirit of the ministry of Jesus Christ in the challenges of the pastoral field in the Timika Diocese. Artikel ini berfokus pada refleksi mengenai panggilan hidup imamat sebagai pelayan di tengah konteks dan situasi pastoral di Keuskupan Timika. Pendekatan yang digunakan adalah studi dokumen gerejani mengenai spiritualitas imamat dalam pelayanan bagi umat Allah. Tujuan dari tulisan ini adalah untuk menemukan semangat pelayanan yang luhur dari seorang imam yang bertolak pada teladan Yesus Kristus sebagai guru dan gembala utama dalam pelayanan pastoral di keuskupan Timika. Pelayanan yang total dalam keterlibatan yang dedikatif, kehadiran yang menyejukkan, masuk dalam pergumulan hidup keluarga, dan berani untuk berdialog dengan siapa pun merupakan pelayanan konkret demi mewujudkan spirit pelayanan Yesus Kristus di tengah tantangan medan pastoral di Keuskupan Timika.